“Sustainable synthesis of Camellia sinensis-mediated silver nanoparticles (CsAgNP) and their anticancer mechanisms in breast cancer cells” - Tamang R.; Mehata A.K.; Singh V.; Muthu M.S.; Koch B. (My University, 2025)
The present investigation focuses on synthesizing eco-friendly and cost-effective silver nanoparticles (CsAgNP) utilizing Camellia sinensis ethanolic extract (CsE) as a reducing agent and investigating the potential enhancement in its anticancer efficacy as compared to CsE. The CsAgNP formation was confirmed through the color change from pale green to dark brown and further validated using UV–visible spectroscopy in the 400-450 nm range. The optimal CsAgNP synthesis parameters include 1:4 ratio of CsE: 1 mM AgNO3, 60 min of duration and 50 °C reaction temperature. The morphology and the size of nanoparticles were estimated using AFM, SEM and TEM where the results showed a smooth topography with a size <100 nm. The CsAgNP crystalline form was confirmed through SAED pictures and silver's presence confirmed through EDX analysis. FTIR study ascertained the capping agents and distortion in functional groups compared to CsE. The anticancer potency of CsAgNP and crude extract (CsE) was assessed against the T-47D breast cancer cells by MTT assay. CsAgNP displayed strong activity towards T-47D cells (IC50 8 μg/ml) compared to CsE and relatively low activity towards the normal HEK-293 cells. Further, fluorescence microscopy and flow cytometry data revealed that the CsAgNP promotes apoptosis and also induces G2-M phase cell cycle arrest. Furthermore, CsAgNP treatment decreases p53 and Bcl-2 protein expression, while increasing Bax, Cytochrome c and Caspase-3 levels, indicating mitochondrial-mediated apoptotic pathway activation. Thus, our research aims to investigate the potential of using Camellia sinensis to synthesize CsAgNP, a potent drug delivery system, to enhance anticancer effectiveness and advance cancer therapy in the future. © 2024 Elsevier B.V.